Professoras e professores rurais em Mato Grosso : entre Várzea Grande e Ponta-Porã na fronteira do estado (1940 -1974) - Rodrigues, Marilu Marqueto (2019)
This research is part of the History of Education, School Institutions and teacher training. It aims to investigate the organization of the Normal Rural School in Mato Grosso, in order to analyze how the creation and installation of the normal rural school, also called the regional school, occurred in the period from 1940 to 1974. The research cut was established at beginning in the 1940s, when discussions about rural education in Brazil expanded. The research period ends in 1974, when the objects of analysis of the research, the normal regional course of the Regional Normal School of Ponta Porã-MT was closed, and the Institute Missionaries Bom Jesus underwent reformulations, modifying the structure of operation of the school institution. We propose to carry out a bibliographical and documentary research. We have as primary sources of research: State Public Instruction Reports, Laws, Decrees, Public Instruction Bulletins, newspapers, photographs, messages of the presidents of the State of Mato Grosso and the Presidents of Brazil, Reports, Constitutions, Letters and Chronicles of the Missionaries Good Jesus. The sources were collected at the Public Archive of Mato Grosso (APMT), in the city of Cuiabá-MT, at the Memory Institute of the Legislative Branch of Mato Grosso, at the Public Archives of the Regional Coordination of Education of Ponta Porã-MS, at the Permanent Archive of the School Adê MarquesMS, in the city of Ponta Porã-MS, in the Living Memory Center of the Institute of Education - CMVIE-UFMT, in the Center Research Libraries, Regional Documentation Center of the Federal University of Grande Dourados-MS and in the Archives of the Missionary Institute of Bom Jesus. We also consulted the scientific production published in books, magazines and periodicals, dissertations and theses related to the subject under study. We tried to answer the following question: How was the Normal Rural School Mato-Grossense organized? We chose for this research the following categories: normal rural school; training of rural teachers and teachers; context of normal rural education in Mato Grosso. We are based on authors such as Jacques Le Goff (1990), Marc Bloch (2002), Justino Pereira de Magalhães (2004), Paolo Nosella and Ester Buffa (2009), who helped us to understand the memory of school institutions. Carlos Ginzburg (2006), Michel de Certeau (1998), Peter Burke (1997), helped us understand that it is possible to analyze aspects of an institution's daily life, to go hunting to find the sources of research. Authors such as Carlos Bacellar (2008), Maria Cecília de Souza Minayo (2007), Alessandra Pimentel (2001), were fundamental to understand procedures of research in the public archives, as well as for the analysis and interpretation of the sources. For the understanding of the history of women, their challenges and achievements, we are based on the authors: Michelle Perrot (2007), Jane Soares de Almeida (2004), Guacira Lopes Louro (1997). Nilce Vieira Campos Ferreira (2014) made possible the understanding of the normal rural schools that were established from the 1950s in Brazil. In order to understand the History of Education we have the works of Otaíza de Oliveira Romanelli (1986), Dermeval Saviani (2008), among others. Rural education is understood from the works of Sud Mennucci (1944), Manoel Bergström Lourenço Filho (2001), Joaquim Moreira de Sousa (1944), Gervásio Leite (1944) and Francisco Alexandre Ferreira Mendes (1944). Although some normal rural schools were created as model schools, the majority lacked adequate conditions for their maintenance and development, that is, although their creation, implantation and organization had a perspective of modernization and progress for the Brazilian rural environment, majority, according to reports and messages from governments and presidents, were precarious in their structures, didactic-pedagogical organizations and functions. It should be noted that in the state of Mato Grosso, until the 1940s, there were only two normal public schools in the urban area which were teachers for primary education. It was only in 1959 that the Regional Normal School of Ponta Porã-MT was founded. The Cristo Rei Normal Rural Women's Institute, in the city of Várzea Grande-MT, which later became known as the Missionary Institute of Bom Jesus was founded only in 1961. Between the years 1959 and 1974, in the state of Mato Grosso, these two schools trained teachers in rural areas, however, we have shown that although they received significant financial resources in the years in which teacher training was offered, the Instituto Missionárias Bom Jesus formed 69 teachers and the Regional Normal School of Ponta Porã, formed 271 rural normal teachers. Throughout the course of formation of the two schools, we have shown an education influenced by conservative religious principles, in which the training offered was almost always based on the minimum curricula, but still an education that provided the training of teachers and teachers to act in the primary series, from 1st to 4th grade, in rural schools in the state of Mato Grosso.